COMPARISON OF PERINATAL OUTCOME OF GROWTH RESTRICTED FOETUSES WITH NORMAL AND ABNORMAL UMBILICAL ARTERY DOPPLER WAVEFORMS - Ali, Azmat; Ara, Iffat; Sultana, Ruqqiya; Akram, Faiza; Zaib, Muhammad Jehan (Journal of Ayub Medical College Abbottabad, 2014)
Background: Intrauterine growth restriction (IUGR) is a complex problem. It is notorious but a difficult diagnosis. The perinatal mortality can be reduced when the results of umbilical artery Doppler are made available to clinicians to help them intervene more timely and appropriately. This study aimed to compare perinatal outcome of growth restricted foetuses with normal and abnormal umbilical artery doppler waveforms. Methods: This cross-sectional descriptive study was conducted in the radiology department of Mother and Child Health (MCH), Pakistan Institute of Medical Sciences (PIMS), Islamabad from March 2007 to March 2008. A total of 100 pregnant women with growth restricted foetuses were studied with umbilical artery Doppler ultrasound. Fifty women had normal umbilical artery Doppler waveform and the umbilical artery Doppler wave-form was compromised (either absent or reversed) in the 50 pregnancies. These patients were followed up and the perinatal outcomes were recorded and compared. Results: Premature delivery was recorded in 14% in the normal group and 96% in the abnormal group. The number of babies with low birth weight was more in the abnormal group. The neonatal intensive care (NICU) admissions were significantly increased in the abnormal group (82%). The incidence of intra-ventricular haemorrhage was more (18%) in the abnormal umbilical artery Doppler group as compared to normal group (06%). Perinatal deaths were three times more in the abnormal umbilical artery Doppler group as compared to normal. The difference in the perinatal outcome of both group is statistically significant (p=.0001). Conclusion: There is a strong relationship between pregnancy outcome in IUGR babies and abnormal uterine artery doppler waveform (Absent or reversed). Keywords: Intrauterine growth restriction, Umbilical artery Doppler waveform, perinatal outcome